2017
DOI: 10.1159/000479200
|View full text |Cite
|
Sign up to set email alerts
|

Istaroxime Inhibits Motility and Down-Regulates Orai1 Expression, SOCE and FAK Phosphorylation in Prostate Cancer Cells

Abstract: Background/Aims: Istaroxime is a validated inotropic Na+/K+ ATPase inhibitor currently in development for the treatment of various cardiac conditions. Recent findings established that this steroidal drug exhibits potent apoptotic responses in prostate tumors in vitro and in vivo, by affecting key signaling orchestrating proliferation and apoptosis, such as c-Myc and caspase 3, Rho GTPases and actin cytoskeleton dynamics. In the present study we examined whether istaroxime is affecting cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…Furthermore, our findings on Orai1 have been compatible with the other studies on various malignancies including breast carcinoma 20 glioblastoma 21 pancreatic adenocarcinoma 25 melanoma 26 , 27 renal carcinoma 28 esophageal squamous cell carcinoma 29 non-small-cell lung carcinoma 30 prostate carcinoma. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings on Orai1 have been compatible with the other studies on various malignancies including breast carcinoma 20 glioblastoma 21 pancreatic adenocarcinoma 25 melanoma 26 , 27 renal carcinoma 28 esophageal squamous cell carcinoma 29 non-small-cell lung carcinoma 30 prostate carcinoma. 31 …”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ]. A previous study using DU145 cells reported that prostate cancer cell migration was regulated by the blockage of ORAI1 by 2-APB, enhancing the therapeutic efficacy of the Na + /K + ATPase inhibitor [ 46 ]. TRPM4 is upregulated in various cancers, and increased intracellular Ca 2+ activates TRPM4, leading to Na + ion influx.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of intracellular Ca 2+ levels may result from the entry of extracellular Ca 2+ as well as the release of sequestered Ca 2+ from intracellular stores such as the ER [27,28]. In non-excitable cells, SOCE is the major pathway for Ca 2+ entry [29,30]. SOCE are plasma membrane Ca 2+ channels activated by a decrease in Ca 2+ content in the ER [31].…”
Section: Discussionmentioning
confidence: 99%